2017
DOI: 10.1159/000472711
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Intra- and Inter-Rater Reliability of Three Methods for Measuring Atopic Dermatitis Severity: EASI, Objective SCORAD, and IGA

Abstract: Background: Numerous different scoring systems have been proposed for assessing the severity of atopic dermatitis (AD). Many of these methods did not undergo proper validation and reliability testing. Objective: The aim of our study was to compare the reliability and reproducibility of the Eczema Area and Severity Index (EASI), objective Scoring Atopic Dermatitis (oSCORAD), and Investigator Global Assessment (IGA). Methods: On the scoring day, 10 trained dermatologists evaluated 10 adult patients with AD using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 22 publications
2
52
0
Order By: Relevance
“…Several objective methods have been used to assess AD severity: SCORAD, Eczema Area and Severity Index (EASI), and Six Area, Six Sign Atopic Dermatitis (SASSAD) . A systematic review indicated that SCORAD and EASI were the most valid and reliable instruments to measure clinical signs of AD with adequate internal consistency and responsiveness .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several objective methods have been used to assess AD severity: SCORAD, Eczema Area and Severity Index (EASI), and Six Area, Six Sign Atopic Dermatitis (SASSAD) . A systematic review indicated that SCORAD and EASI were the most valid and reliable instruments to measure clinical signs of AD with adequate internal consistency and responsiveness .…”
Section: Discussionmentioning
confidence: 99%
“…Sign Atopic Dermatitis (SASSAD). [24][25][26] A systematic review indicated that SCORAD and EASI were the most valid and reliable instruments to measure clinical signs of AD with adequate internal consistency and responsiveness. 16 However, they are time-consuming and too complex to use every day, because they are based on physician assessment in the outpatient clinic at different intervals over a few months.…”
Section: Discussionmentioning
confidence: 99%
“…We also used two additional disease severity metrics. Reduction in IGA score (Supplementary Tables 2) [18] was assessed to determine treatment success rate, defined as the percentage of patients whose IGA score was reduced to 0 (clear) or 1 (almost clear) after the end of the treatment. Pruritus alleviation was assessed using the visual analogue scale score of 2.6.…”
Section: Efficacy Evaluationmentioning
confidence: 99%
“…Additionally, these Investigator Global Assessment (IGA) tools have the clear advantage that patients are more likely to understand the meaning of the words associated with each score (the most common being “clear”, “almost clear”, “mild”, “moderate” and “severe”) rather than a SCORAD or EASI value of 20. Although a systematic review confirmed the availability of numerous global scales for the evaluation of atopic skin lesions in humans, their validation is limited, and there is an unfortunate lack of standardization between tools …”
Section: Introductionmentioning
confidence: 99%